تصميم نظام متسامح العطل في حساسات الصورة (حساسات البكسل الفعالة (APS)) - العلي, علي; البستاني, حسن; حبيب, علاء رافع (Latakia University Journal -Engineering Sciences Series, 2019)
In this research, we are dealing with Digital video systems and digital Cameras that have a very important improvement during last years, like using the new CMOS (complementary metal-oxide semiconductor) Image Sensor instead of traditional Image Sensor CCD (Charge Coupled Devices). Even though the progress in CMOS technology offers the means to fabricate them, smaller pixels in advanced technologies must overcome some electrical and optical problems, and this is what we presente by designed a fault tolerance Active Pixel Sensor using hardware redundancy called TMR (Triple Modular Redundancy). We designed a CMOS Image Sensor with our TMR that contains analog comparator, the next step was making a modification in the structure of the classic TMR to decrease the cost of fabricate on the chip, then we analyze the Reliability of entire system and compare the results with the reliability of single Image Sensor تصميم نظام متسامح العطل في حساسات الصورة (حساسات البكسل الفعالة (APS)) يهتم البحث بأنظمة الفيديو (Video Systems) والكاميرات الرقمية والاتجاه نحو حساسات الصورة (Image Sensor) من صنف CMOS (complementary metal-oxide semiconductor) كبديل عن الحساسات من صنف CCD Charge Coupled Devices)) نظراً للميزات التي تتمتع بها من حيث إمكانية التصنيع على نفس الشريحة مع الدارات المرافقة للحساس بالإضافة إلى صغر الحجم والاستهلاك المنخفض للطاقة. تساعد المميزات المذكورة تقنية CMOS على تقديم عنصر صورة (Pixel) صغير الحجم وذو تقنية متطورة, إلا أنها يجب أن تتغلب على بعض العيوب الإلكترونية والضوئية, وهذا ما نقدمه من خلال تصميم حساس عنصر صورة نشط (Active Pixel Sensor) بتطبيق تقنية الفائضية ثلاثية النماذج (Triple Modular Redundancy), وذلك من خلال تصميم حساس الصورة ومن ثم إدخال التقنية المذكورة, بعد ذلك تعديل التصميم لتقليل عدد الترانزستورات على شريحة الحساس تم أيضاً تحليل الوثوقية (Reliability) للنظام المقترح ومقارنته مع وثوقية الحساس منفرداً لتحديد مستوى التحسين الحاصل في الوثوقية والتي تعد مع تسامحية العطل مؤشراً هاماً على تحسين الاعتمادية (Dependability) للنظام عامة.